The impact of Hanen More Than Words Programme on parents of children with ASD in Malaysia - Sherin Sokmun,; Susheel Kaur Dhillon Joginder Singh,; Sandra Vandort, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study aims to investigate the viability and effectiveness of the Hanen More Than Words (HMTW) programme amongst parents of children with Autism Spectrum Disorder (ASD). This quassi-experimental study involved 31 children (27 boys, 4 girls; M = 34.58 months, SD = 3.67) who met criteria for ASD and their parents. The measurement was conducted in three phases; Time 1 (prior to intervention), Time 2 and Time 3 (at three and five months after the intervention begins). The outcome measures were assessed based on: (1) changes in parental facilitative strategies; (2) the children’s growth in vocabulary and (3) the progress of communication and social skills. The paired t-test were used to analyze the pre and post findings within the intervention and control group with p-value <.01. Results showed that there was an increase in using the facilitative communication strategies by parents in the HMTW group during parent-child interaction. The children showed an increased in vocabulary, communication and social skills. The parents agreed that their mastery of facilitative communication strategies increased and they provided positive feedback about the HMTW approach. The results suggested that the HMTW program could be implemented well by Malaysian parents. The training was supported by Malaysian parents and had measurable effect on both parents and children.